STUDIES ON FOLIAR APPLICATION OF GROWTH REGULATORS AND CHEMICALS ON SEEDLING GROWTH OF MANGO VARIETIES - B. M. MURALIDHARA,; Y. T. N. REDDY,; M. K. SHIVAPRASAD,; H. J. AKSHITHA,; MAHANTHI, KISHOR KUMAR (The Bioscan, 2014)
A field experiment was carried out to study the effect of foliar application of growth regulators and chemicals on seedling growth of mango varieties. Among the varieties used Bappakkai recorded the maximum seedling height (30.4 cm), girth (0.83 cm), number of leaves (15.0), leaf area (460.4 cm2), fresh weight (36.55 g), dry weight (14.38 g), internode elongation (4.49 cm) and per cent of graftable seedlings (86.6 %) and minimum was in variety Olour (22.3 cm, 0.62 cm, and 13.9, 196.2 cm2, 15.86 g, 5.62 g, 4.49 cm and 39.1 % respectively). Among the treatments, the maximum plant height (32.1 cm), intermodal length (9.26 cm) and dry weight (11.57 g) was recorded in GA3 300 ppm while the other treatment nitrophoska 0.2 per cent noticed maximum leaf area (408.5 cm2) and fresh weight (30.25 g). The number of leaves (16.4), stem girth (0.78 cm) and per cent of graftable seedlings (73.3 %) was maximum in benzyl adenine 50 ppm, GA3 200 ppm and benzyl adenine 75 ppm respectively and minimum was noticed in control. In interaction the variety Bappakkai seedlings sprayed with GA3 300 ppm recorded maximum plant height (35.9 cm), girth (0.93 cm) and per cent of graftable seedlings (100 %) whereas Bappakkai seedlings sprayed with GA3 200 ppm noticed maximum fresh (48.7 g) and dry weight (18.2 g) and the Olour seedlings sprayed with benzyl adenine 50 ppm and GA3 300 ppm recorded the maximum number of leaves (18.0) and intermodal length (9.46 cm) respectively. The GA3 200 and 300 ppm spray helps to obtain more graftable seedlings in the varieties Olour and Bappakai respectively.